Strategic Agility and its Impact on Organizational Supply Chain Success: Applied Research in a Sample of the Faculties of the University of Babylon - Zafar Nasser Hussain; Zainab Abdel Razzaq Abood; Ahmed Hadi Talib (International Journal of Supply Chain Management, 2018)
The current research aims to answer the following questions: Is there a relationship between strategic agility and organizational supply chain success? Is there an impact of strategic agility on organizational supply chain success? Through the theoretical philosophy and the intellectual implications of these variables and through the practical application of the research sample, which represented the faculties of the University of Babylon, (15) faculty, the questionnaire was distributed to the actors in these colleges and the deans of the faculties and assistants deans and heads of departments, The research came out with the most important conclusions were the existence of a relationship of significant significance and the existence of a significant effect of the strategic agility in organizational supply chain success.